Information System for Monitoring High-Risk Pregnant Women - Anisa Nurul Wilda; Yasmini Fitriyati; Izzati Muhimmah (IJID (International Journal on Informatics for Development), 2021)
Maternal mortality rates are still high in several areas, including Bantul Regency, Special Region of Yogyakarta. Based on the data obtained from the Bantul District Health Office, from 2018 to 2019, 28 pregnant women died. Posyandu and Puskesmas cadres often encounter problems in collecting data on pregnant women because they still use manual methods. Manual records using books has disadvantages because sometimes pregnant women forget to bring their books. Therefore, an application for recording pregnancy history is needed to enable convenient monitoring by Posyandu cadres, Puskesmas, doctors, and hospitals in order that pregnant women patients can be handled properly in case of emergency. The application used by pregnant women is Mobile App-based, meanwhile, the Web-based Monitoring Information System is used by Posyandu cadres, Puskesmas, doctors, and hospitals. The application allows displaying the medical history and makes it easier for pregnant women to have counseling or examinations without meeting directly with the doctor. If there are any problems in the womb, the doctor will immediately provide a solution or recommendation. The results of the system testing with 15 respondents as users show that 52,1% strongly agree, 37,7% agree, and 10,2% neutral in response to the system interface. The implementation of the information system for monitoring high-risk pregnant women in the majority is accepted by all actors. Hence, it can be concluded that in an attempt to digitalize manual recording of pregnant women's examinations, this information system for monitoring high-risk pregnant women is reliable to be implemented.